An introduction to Islamic philosophy - Campanini, Massimo, 1954- (Edinburgh University Press, 2008)
This broad, comprehensive, and yet concise introduction presents a reading of Islamic philosophy as it evolved in the Middle Ages, investigating how Islamic philosophers thought and what they thought about. The book is divided into two parts: the first part explores the epistemological foundations of Islamic philosophy and discusses the most important and penetrating interpretative paradigms proposed by the philosophers; the second part describes some of their major themes. Each chapter is organised chronologically and geographically, providing the reader with a lucid profile of the evolution of Islamic philosophical thought, with reference to specific themes within the broader framework of Islamic history. Throughout the author includes extracts of translations from primary sources, allowing the philosophers to speak for themselves. Rather than offering a complete history of the subject, the author aims to stimulate the reader to pursue the themes he outlines in the book: the ideas that were consistently the object of philosophical speculation among Medieval Muslim thinkers whose philosophy was rooted in Platonic and Aristotelian thought.This book is ideal for students wishing to trace the background to many ideas and thought processes governing contemporary Islamic thought.